2014
DOI: 10.1080/00986445.2014.912637
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method to Determine the Resistance of Biotemplated Nanowires

Abstract: Genetically engineered Tobacco Mosaic Virus (TMV) was coated with uniform layers of palladium metal particles in aqueous solution without the aid of an external reducing agent while producing nanowires of 300 nm in length and 30-60 nm in diameter. By combining a gold nanogap approach and electron beam assisted Pt deposition approach, an innovative electrical characterization technique has been developed in order to determine the resistance of a single Pallidium-Tobacco Mosaic Virus (Pd-TMV) nanorod. The prelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Nanostructures are increasingly sought to create advanced materials that improve electrical conductivity and capacitance, current generation, catalytic activity, and detection sensitivity. [3,5,19,49,50] These applications benefit from high aspect ratio nanomaterials that can be biotemplated on TMV or its VLPs. However, each application relies on distinct metals whose unique electronic structure is key to enabling these applications, for example, metal with high conductivity such as copper is used in conductive nanowires while gold is relatively inert making it an ideal substrate for a sensor.…”
Section: Nanostructure Synthesis With Viral Biotemplates For Diverse mentioning
confidence: 99%
“…Nanostructures are increasingly sought to create advanced materials that improve electrical conductivity and capacitance, current generation, catalytic activity, and detection sensitivity. [3,5,19,49,50] These applications benefit from high aspect ratio nanomaterials that can be biotemplated on TMV or its VLPs. However, each application relies on distinct metals whose unique electronic structure is key to enabling these applications, for example, metal with high conductivity such as copper is used in conductive nanowires while gold is relatively inert making it an ideal substrate for a sensor.…”
Section: Nanostructure Synthesis With Viral Biotemplates For Diverse mentioning
confidence: 99%
“…Nanostructures are increasingly sought to create advanced materials that improve electrical conductivity and capacitance, current generation, catalytic activity, and detection sensitivity [3,5,19,46,47]. These applications benefit from high aspect ratio nanomaterials that can be biotemplated on TMV, BSMV or their VLPs.…”
Section: Nanostructure Synthesis With Viral Biotemplates For Diverse Applicationsmentioning
confidence: 99%
“…Directed synthesis of nanomaterials with controllable dimensions remains a subject of immediate concern in nanotechnology. , Biotemplating, the use of naturally occurring biomolecules to develop nanomaterials of similar morphology, hierarchical complexity and nanometric precision, is a viable means to easily and inexpensively produce needed nanomaterials on a large scale . Specifically, the use of viruses as biotemplates has been pursued as a potent solution due to their unique advantages for applications in catalysis, nanocircuitry, chemical sensing, biocatalysis, memory devices, and light harvesting. , As many studies of the M13 bacteriophage and the Tobacco mosaic virus (TMV) have shown, virus templates are particularly exciting due to the wide range of chemical interactions afforded by their multifunctional protein surfaces. The potential presence of polar, hydrophilic, charged, acidic, and basic functionalities on a single template allow the formation of a wide range of inorganic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%